Sip to Healthy Smile: The Enchanting Dental Wonders of Green Tea - Shete, Mrinal; Shete, Anagha; Gondkar, Gauri Umesh (Disease and Health Research: New Insights Vol. 9, 2024)
The utility of natural products is increasingly in demand for medical purposes. One of the abundant natural materials is green tea leaves (Camellia sinensis L. Kuntze) which has many health benefits [1]. Green tea is a popular beverage consumed widely in the world for thousands of years and is considered traditional Chinese Medicine [2]. Green tea contains a variety of bioactive agents with many health benefits. Tea has positive health benefits and helps in pathologic changes prevention and maintaining health conditions. Green tea promotes periodontal health by limiting the growth of bacteria associated with periodontal disease. Also, Green tea has properties like solar ultraviolet protection, bone mineral density, anti-fibrotic and neuroprotective power [2]. It has been reported that green tea has a role in the prevention of dental erosion, dental caries, alveolar bone resorption, oral malodour etc. Also, it protects against various malignant, cardiovascular and metabolic disorders. Polyphenols, a constituent of green tea, are contributing factors in the prevention of cancer and other diseases [3]. Numerous studies have shown beneficial effects in maintaining oral health on regular intake of Green Tea. Green tea also increases basal metabolic rate. Green tea contains more catechins as it is a non-fermented tea, compared to black tea or Oolong tea [2].